PENGARUH MOTIVASI DAN PENGALAMAN KERJA TERHADAP KEDISIPLINAN KERJA (Studi Pada Karyawan Toko Belanja Sardo Swalayan Kota Malang) - Moh Basyiruddin; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study was conducted to determine the effect of motivation and work experience on employee work discipline at Sardo Swalayan, located at Jalan Gajayana no.500, Dinoyo, Lowokwaru District, Malang City, East Java 65145. The method used is a quantitative method used to examine a population or specific sample that aims to explain the position of each variable and its effect between one variable with another variable, and the source of the data used is primary data by spreading Likert scale kusieoner to Sardo Shopping Shop Employees City of Malang supermarket. The sample calculation in this study uses the Slovin formula which produces 49 respondents. The results of this study are the variables of motivation and work experience simultaneously and partially affect work discipline. Keywords: Motivation, Work experience, Work Discipline